INTERNAL MARKETING: USING MARKETING-LIKE APPROACHES TO BUILD BUSINESS COMPETENCIES AND IMPROVE PERFORMANCE IN LARGE MALAYSIAN CORPORATIONS - Norizan M. Saad; Pervaiz K. Ahmed; Mohammed Rafiq (Asian Academy of Management Journal, 2002)
This study was conducted to make substantial progress in building theory about customer-focused organisations and its impact on business competencies and performance. To date, it is the first empirical attempt to gain knowledge on internal marketing (IM) implementation using a 'marketing-like' approach. The results of the study suggest that this approach is imperative to create organisational competencies and business performance. This study therefore serves to develop and test a conceptual model linking IM mix components, competencies and business performance that adds knowledge to the IM implementation framework in particular and other organisational development theories in general.